Information Intermediaries and Information Resilience: Working to Support Marginalised Groups. Issue 1 (14th October 2022) - Nicol, Emma; Willson, Rebekah; Ruthven, Ian; Elsweiler, David; Buchanan, George
ABSTRACT: Information resilience has become a topic of interest to the information science community in recent years. The COVID‐19 pandemic has shone a light on the vulnerability of information and other networks and the impact on information providers and the information seekers who rely on them. In an exploratory study, we interviewed support workers who act as information intermediaries as part of their work roles about their experiences of providing information to vulnerable and marginalised people during the UK COVID‐19 lockdown. We present findings organised in three themes: shifting client information needs and support provisions, adjusting information sharing and communication practices and workarounds for physical information work. Throughout the themes, information resilience is evident as information intermediaries adapt their work practices to ensure they can continue to serve their clients. In this first stage of research our findings provide insight into the changes to information intermediaries' information behaviour and information work during a crisis, as well as the impact of these changes on the services they provide.